Surface Reduction Mechanism of Cerium-Gallium Mixed Oxides with Enhanced Redox Properties - Vecchietti, María Julia (2013)
The doping of CeO2 with different types of cations has been recognized as a significant factor in controlling the oxygen vacancies and improving the oxygen mobility. Thus, the catalytic properties of these materials might be determined by modifying the redox properties of ceria. A combined experimental and theoretical study of the redox properties of gallium-doped cerium dioxide is presented. Infrared spectroscopy and timeresolved X-ray diffraction were used for temperature programmed reduction (H2) and oxidation (with O2 and H2O) studies. Additionally, X-ray absorption near edge spectroscopy shows that only Ce4+ is reduced to Ce3+ in the ceria-gallia mixed oxides when annealed up to 623 K. The oxygen storage capacity (OSC) measurements show a pronounced enhancement on the reduction of ceria by gallium doping. Theoretical calculations by density functional theory (DFT) confirm the higher reducibility of gallium-doped ceria oxides and give a molecular description of the stabilization of the doped material. On the basis of infrared spectroscopic measurements, a novel mechanism is proposed for the surface reduction of Ce4+ to Ce3+ where Ga−H species are suggested to be directly involved in the process. In addition, the reoxidation by H2O was precluded in the galliumdoped ceria oxide.